2022
DOI: 10.3389/fmicb.2021.636639
|View full text |Cite
|
Sign up to set email alerts
|

The Biogeography of Fungal Communities Across Different Chinese Wine-Producing Regions Associated With Environmental Factors and Spontaneous Fermentation Performance

Abstract: Chinese Marselan grapes are believed to possess the potential to become a characteristic regional variety, whose quality is internationally recognized. The fermentation-related mycobiota from six climatically diverse Marselan-producing regions in China were analyzed via high-throughput sequencing (HTS), while the influence of environmental factors was evaluated as well. The results implied that the phyla Ascomycota and genus Aureobasidium dominated the fungal communities in 166 Marselan must and fermented samp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 44 publications
2
17
0
Order By: Relevance
“…Country of origin, the region of isolation of the samples, is the most influential layer. This evidence confirms what has been reported in other studies, where both single- and multiple-cultivar analysis highlighted that fungal microbiome correlates with regional grape microbial patterns [ 5 , 8 , 9 , 10 , 17 , 18 , 20 ]. Since the initial treatment of the data, datasets coming from the different localizations show specific characteristics in the form of different abundances, richness, or number of unidentified fungi.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Country of origin, the region of isolation of the samples, is the most influential layer. This evidence confirms what has been reported in other studies, where both single- and multiple-cultivar analysis highlighted that fungal microbiome correlates with regional grape microbial patterns [ 5 , 8 , 9 , 10 , 17 , 18 , 20 ]. Since the initial treatment of the data, datasets coming from the different localizations show specific characteristics in the form of different abundances, richness, or number of unidentified fungi.…”
Section: Discussionsupporting
confidence: 91%
“…Different single-cultivar studies analyzed intra-varietal microbial differences within smaller [ 6 , 8 , 10 , 16 ] or larger [ 4 , 5 , 9 , 15 , 17 , 18 ] areas, focusing on bacterial [ 8 , 10 ] or fungal [ 6 , 9 , 15 , 16 , 17 , 18 , 19 ] composition, or analyzing both groups of microorganisms [ 4 , 5 ]. In particular, some works estimated the differences in microbial biodiversity linked to vineyard management and spatial or biological niches (bulk, fruit, leaves, and soil) [ 5 , 8 , 9 , 10 , 15 , 17 , 18 , 19 ]. The results demonstrated that species richness and biodiversity are influenced by viticultural practices [ 4 , 5 , 6 , 16 ], and operational taxonomic units (OTU) peculiar to specific farming system were described [ 6 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Prince grape must, the most abundant genus was Hanseniaspora . In addition, fungal genera such as Starmerella , Cladosporium and Alternaria , which were common in Chinese wine-producing regions, were also detected in grape must [ 21 ]. With the progress of wine fermentation, the two groups of S. cerevisiae rapidly proliferated and dominated the alcoholic fermentation.…”
Section: Resultsmentioning
confidence: 99%
“…The main fungal communities in Cannonau grape must in the Sardinia region of Italy were Aureobasidium , Alternaria and Hanseniaspora [ 28 ]. For Marselan grape must, the dominant fungal communities in the Huailai wine-producing region of China were Aureobasidium and Alternaria [ 21 ]. We analyzed the fungal genera in Prince grape must, and the results showed that Hanseniaspora and Cladosporium were the dominant fungal genera in the grape must.…”
Section: Discussionmentioning
confidence: 99%